Evaluation of efficacy of arthrocentesis (with normal saline) with or without sodium hyaluronate in treatment of internal derangement of TMJ – A prospective randomized study in 20 patients - Aditi Sharma; Amar Singh Rana; Gaurav Jain; Puneet Kalra; Deepak Gupta; Siddharth Sharma (Journal of Oral Biology and Craniofacial Research)
Purpose: To compare the outcome of arthrocentesis alone and arthrocentesis with sodium hyaluronate in internal derangement of TMJ. Materials and methods: 20 patients of disc displacement with reduction of TMJ were randomized into 2 experimental groups. Control group of patients received arthrocentesis alone and study group of patients received arthrocentesis with sodium hyaluronate. Patients TMJ status and clinical symptoms were evaluated for 6 months follow up. The clinical parameter recorded were maximal mouth opening (MMO), lateral excursions (right and left side), protrusive movement, joint noises, and pain (at rest, at function). Results: When 2 groups are compared there was no statistically significant difference in terms of inter-incisal opening, lateral excursion, protrusive movement, joint noises and pain however the group with sodium hyaluronidase has shown better results than the control group. Conclusion: Both study and control group found to be statistically insignificant but patient who were in the group of arthrocentesis with admission of sodium hyaluronidase had better results.